Community Malaria Knowledge, Experiences, Perceived Roles, and Acceptability of Community-Directed Distribution of Intermittent Preventive Therapy for Pregnancy in Rural Southeast Nigeria. (18th January 2022) - Okedo-Alex, Ijeoma Nkem; Akamike, Ifeyinwa Chizoba; Nwafor, Johnbosco Ifunanya; Alo, Chihurumnanya; Agu, Adaoha Pearl; Abateneh, Dejene Derseh; Uneke, Chigozie Jesse
Abstract : Background . The community plays key roles in protecting pregnant women in rural areas from malaria. This study assessed malaria experiences, knowledge, perceived roles in malaria prevention in pregnancy, and acceptability of community-directed distribution of intermittent preventive therapy (IPTp) for malaria in pregnancy in rural Southeast Nigeria. Methods . This study presents part of the baseline findings of a before-and-after study. Data was collected from 817 community members in Ebonyi State using interviewer-administered questionnaires and focus group discussions (FGDs). Data were analyzed using SPSS version 20 and thematic analysis. Results . The majority of the respondents were females (73.8%) with a mean age of 36.08 ± 15.4 . Most respondents (65.2%) had Insecticide-Treated Net (ITN) and fever in the past year (67.1%). Malaria (88.6%) was identified as the major health condition in the community. Majority (74.1%) knew infected mosquito bites as the cause of malaria while 61.1% and 71.5% were definitely sure that pregnant women and children were at risk for malaria. Sleeping under ITN (54.3%), clean environment (39.7%), and herbal medications (26.8%) were the main ways of malaria prevention cited. Only 18.4% of the participants rated their knowledge of IPTp as adequate, and only 9.3% knew the common drug names used for IPTp. The major perceived roles in malaria prevention in pregnancy were referral of pregnant women to the health facility, encouragement of household ITN use, and sustaining malaria-related projects. The majority of the participants (60.6%) strongly agreed that community-directed distribution of IPTp-SP will improve the prevention of malaria in pregnancy. Most (77.2%) considered community-directed distribution of IPTp acceptable, and 74.4% of the pregnant respondents preferred community to facility administration of IPTp. Conclusions . Malaria was recognized as a prevalent disease, but there was inadequate knowledge of malaria prevention in pregnancy notably intermittent preventive therapy. There was positive perception of roles in malaria prevention in pregnancy and high acceptability of community-directed distribution of IPTp. Community-level malaria control programs should utilize a whole-of–community approach to optimally engage and educate the community on malaria prevention in pregnancy as well as explore community distribution approach for IPTp.